Factors associated with the uptake and utilisation of diabetic retinopathy screening services in sub-Saharan Africa: A scoping review. - Iheanyi Oby Nwaoha; Albain Ayime Balibuno; Nuha Ibrahim (PLoS ONE)
Introduction Diabetic Retinopathy (DR) is a microvascular complication of chronic Diabetes that can lead to visual impairment if left untreated. While concerted efforts have been made to develop screening modalities to facilitate the early detection of Diabetic Retinopathy in sub-Saharan Africa, little is known about the factors impacting the optimal use of these screening services. This paper aims to identify and highlight factors associated with the access of Diabetic Retinopathy screening services from patient and service provider perspectives. Methodology This scoping review was conducted using the Arksey and O'Malley (2005) framework. A comprehensive search of peer-reviewed articles and grey literature was conducted from May 2023 to June 2023. Electronic databases searched include Medline, Embase, PubMed, CINAHL Complete, APA PsycINFO, Web of Science, and African Journal Online (AJOL). Two reviewers independently screened the retrieved records for eligibility, and relevant data was extracted from the included studies. A descriptive overview of key findings was provided, and the 5As conceptual framework of access to healthcare was used to map the identified factors. Results The search strategy yielded 873 records. Of those, 19 studies met the criteria for inclusion. Health literacy and duration of Diabetes were reported in 12 and 9 studies as the most common factors associated with DR screening services access. Similarly, age at onset and inadequate referral by healthcare providers were cited as significant determinants of DR screening access in 7 studies, respectively. Conclusion The 5As framework of access to healthcare aids our understanding of factors associated with the access of DR screening from patient and service provider standpoints. To address these issues, there is a need for more research on this topic to design effective DR screening services in the region.